Cycle aging studies of lithium nickel manganese cobalt oxide-based batteries using electrochemical impedance spectroscopy. (20th May 2018) - Maheshwari, Arpit; Heck, Michael; Santarelli, Massimo
Abstract: The cycle aging of a commercial 18650 lithium-ion battery with graphite anode and lithium nickel manganese cobalt (NMC) oxide-based cathode at defined operating conditions is studied by regular electrochemical characterization, electrochemical impedance spectroscopy (EIS) and post-mortem analysis. The study finds that capacity fade, impedance rise and the end-of-life of cycled cells strongly depend on the operating conditions like temperature, current rate, depth-of-discharge and mean state-of-charge. In general, the capacity fade is characterized by a slow linear decrease at first, followed by a rapid decrease. This transition point is found to correlate well to the rate of solid electrolyte interphase (SEI) resistance growth at the anode. A longer lifetime is found for cells cycled at 45 °C than at 20 °C for the same depth-of-discharge and C-rate. Effect of cycle depth on capacity fade is related to the graphite electrode volume changes and the local electrochemical potential at the electrodes. Cells cycling upto 4.2 V are found to have longer linear capacity fade but a higher total resistance. A more stable SEI at the anode and greater surface modifications on the cathode are inferred to be the reasons for this non-intuitive behaviour.